1994
DOI: 10.1002/jmri.1880040113
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative MR relaxometry study of muscle composition and function in duchenne muscular dystrophy

Abstract: Magnetic resonance imaging and maps of T1 and T2 values were used to study muscle composition in Duchenne muscular dystrophy (DMD). The mean T2 of anterior tibial muscle was 27 msec in healthy control subjects and 43 msec with increased fatty infiltration in DMD patients. In stronger DMD patients, the distribution of muscle T2 values was narrow, centered at 27 msec as in the controls, with a nonoverlapping fat peak centered at 49 msec. In weaker DMD patients, the width of the muscle T2 peak increased and the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
96
1

Year Published

1996
1996
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(102 citation statements)
references
References 15 publications
5
96
1
Order By: Relevance
“…[22][23][24][25][26][27][28] Previous MRI studies have demonstrated that dystrophic muscles have higher T2 relaxation times, 10,11,17 even in young boys with DMD. 15 Elevated T2 in dystrophic muscles has been linked to both the presence of muscle damage/inflammation and fatty tissue infiltration.…”
Section: Impact Of Initiation Of Corticosteroid Therapy In Boysmentioning
confidence: 99%
See 2 more Smart Citations
“…[22][23][24][25][26][27][28] Previous MRI studies have demonstrated that dystrophic muscles have higher T2 relaxation times, 10,11,17 even in young boys with DMD. 15 Elevated T2 in dystrophic muscles has been linked to both the presence of muscle damage/inflammation and fatty tissue infiltration.…”
Section: Impact Of Initiation Of Corticosteroid Therapy In Boysmentioning
confidence: 99%
“…15 Elevated T2 in dystrophic muscles has been linked to both the presence of muscle damage/inflammation and fatty tissue infiltration. [11][12][13]25 Since the presumed mode of action of corticosteroids involves the suppression of inflammation, we examined their effects on skeletal muscle T2, using both T2 mapping and 1 H spectroscopic relaxometry. To our knowledge, there is only one previous study that used MRI techniques to study the effects of corticosteroids on skeletal muscles of boys with DMD.…”
Section: Impact Of Initiation Of Corticosteroid Therapy In Boysmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, we measured the magnetic resonance (MR) transverse relaxation (T 2 ) rates of multiple lower leg muscles because of their sensitivity to alterations in intramuscular fat 11 and the demonstrated enhancement in muscle T 2 in animal models of incomplete SCI. 12 …”
Section: Introductionmentioning
confidence: 99%
“…MRI has been used to assess skeletal muscle injury (33,41,43) in studies of DMD patients (24,42) and mdx mice (46,48). Conventionally, skeletal muscle injury is revealed best by T 2 -weighted MRI, which optimizes contrast between edema and muscular tissue (16,50).…”
mentioning
confidence: 99%